IMPROVEMENT OF EFFICIENCY OF GREY CAST IRON MODIFICATION DUE TO INTRODUCTION OF CARBON MODIFIER INTO COMPOSITION - G. F. Lovshenko; O. S. Komarov; N. I. Urbanovich; V. I. Volosatikov; V. S. Niss; A. I. Letsko (Литьë и металлургия)
It is shown that introduction carbon into modifier composition and increase of its dispersion degree due to spatter on high-melting particles or due to mechanical alloying increases modifier efficiency for grey cast iron.